2018
DOI: 10.1038/s41386-018-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Ventral midbrain astrocytes display unique physiological features and sensitivity to dopamine D2 receptor signaling

Abstract: Astrocytes are ubiquitous CNS cells that support tissue homeostasis through ion buffering, neurotransmitter recycling, and regulation of CNS vasculature. Yet, despite the essential functional roles they fill, very little is known about the physiology of astrocytes in the ventral midbrain, a region that houses dopamine-releasing neurons and is critical for reward learning and motivated behaviors. Here, using a combination of whole-transcriptome sequencing, histology, slice electrophysiology, and calcium imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 71 publications
(73 reference statements)
9
62
1
Order By: Relevance
“…Whether this effect in OB astrocytes is mediated by D 1 -D 2 heteromers, as shown in striatal neurons 34 , or by independent D 1 and D 2 receptors is not known and needs further investigation. In contrary to our results, studies in the hippocampus and ventral midbrain have shown that activation of D 2 receptors leads to a decrease in cytosolic calcium, whereas D 1 receptors mediate a calcium rise 29,35 . The D 2 -class receptor-mediated decrease in calcium in hippocampal astrocytes presumably results from modulation of L-type voltage-gated calcium channels 29 , which has also been shown in nucleus accumbens neurons 36 .…”
Section: Dopamine Induces Calcium Transients In Olfactory Bulb Astroccontrasting
confidence: 99%
See 2 more Smart Citations
“…Whether this effect in OB astrocytes is mediated by D 1 -D 2 heteromers, as shown in striatal neurons 34 , or by independent D 1 and D 2 receptors is not known and needs further investigation. In contrary to our results, studies in the hippocampus and ventral midbrain have shown that activation of D 2 receptors leads to a decrease in cytosolic calcium, whereas D 1 receptors mediate a calcium rise 29,35 . The D 2 -class receptor-mediated decrease in calcium in hippocampal astrocytes presumably results from modulation of L-type voltage-gated calcium channels 29 , which has also been shown in nucleus accumbens neurons 36 .…”
Section: Dopamine Induces Calcium Transients In Olfactory Bulb Astroccontrasting
confidence: 99%
“…However, tuning of olfactory information processing and odor perception by neuromodulators such as dopamine, noradrenaline, acetylcholine and serotonin has moved into the focus of research on olfaction, in particular in recent years 23,[57][58][59] , and it is becoming increasingly clear that astrocytes have to be considered to take actively part in these processes. This hypothesis appears to be supported by findings showing interactions of dopamine and astrocytes in other regions of the CNS, such as ventral midbrain and hippocampus 29,35 .…”
Section: Scientific Reports |mentioning
confidence: 61%
See 1 more Smart Citation
“…Midbrain contains not only mDA neurons, a functional cell type representative of the midbrain, but also several other cell types, such as different neuronal subtypes, astrocytes, and oligodendrocytes, which exert roles in maintaining the functional homeostasis of the midbrain . Thus, we next investigated the cellular composition of DAC3.0 MOs.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have indicated that oligodendrocytes express transporters that are permissible to glutamate and glutamine, such as EAAC1 (DeSilva et al, 2009), SNAT3 (Marques et al, 2018), and ASCT2 (Scopelliti et al, 2018), which would allow for a direct exchange of GS substrates with axons. Furthermore, we previously reported extensive gap junction coupling between midbrain oligodendrocytes and astrocytes (Xin et al, 2019). As molecules smaller than 1 kDa can theoretically pass freely through gap junctions (Berg et al, 2002), these structural connections may enable exchange of GS substrates between astrocytes and oligodendrocytes and thus neurons by way of astrocyte transporters.…”
Section: Discussionmentioning
confidence: 99%